Interfacial Action of Co-Doped MoS2 Nanosheets on Directional Piezoelectric Catalytic Generation of Reactive Oxygen Species - Win Thi Yein; Dong-Su Kim; Qun Wang (Chemistry Proceedings, 2024)
Molybdenum disulfide (MoS2) with single- and odd-numbered layers is a novel piezocatalyst, and its piezocatalytic molecular oxygen activation is considered a promising and low-cost strategy for environmental remediation. In this study, the odd-numbered layers of Co-doped MoS2 ultrathin nanosheets were successfully fabricated, which decomposed tetracycline by 99.8% in 15 min through shaking vibration. Moreover, to verify the enhanced piezoelectric catalytic activity of MoS2 via the doping effect, molecular oxygen activation properties were predicted through DFT calculation and monitored by generated reactive oxygen species (ROS) evolution. In addition, the primary reactive species responsible for the degradation of tetracycline pollutants were also investigated in detail.